Adamantinomatous craniopharyngiomas express tumor stem cell markers in cells with activated Wnt signaling: further evidence for the existence of a tumor stem cell niche? - Hölsken, Annett; Stache, Christina; Schlaffer, Sven-Martin; Flitsch, Joerg; Fahlbusch, Rudolf; Buchfelder, Michael; Buslei, Rolf (Pituitary, 2014)
Early disease onset, clinical manifestation, histomorphology, and increased tendency to relapse distinguish the adamantinomatous craniopharyngioma (adaCP) from the more favorable papillary variant (papCP). A molecular hallmark of adaCP is the activated Wnt signaling pathway indicated by nuclear ?-catenin accumulation in a subset of tumor cells. A mouse model recently illustrated that these cells are the driving force in tumorigenesis of adaCP. This observation and the peculiar growth pattern points to the existence of a specific tumor stem cell (TSC) population in human CP.To prove this hypothesis, the TSC markers CD133 (Prominin1) and CD44 were examined in papCP (n = 8) and adaCP (n = 25) on mRNA level using quantitative real time PCR of total tumor RNA. Furthermore, we investigated protein expression performing immunohistochemical analyses of formalin-fixed paraffin embedded tumor samples.PapCP revealed a homogenous CD44 expression pattern predominantly at the cell membrane, whereas CD133 labeling was hardly detectable. In adaCP, on the other hand all markers were consistently and predominantly co-expressed in nuclear ?-catenin accumulating cell clusters, which was confirmed by double immunofluorescence staining. Overall expression of CD44 was significantly decreased in adaCP versus papCP, whereas CD133 showed significantly higher protein and mRNA levels in adaCP.Our results indicate tumor stem cell-like characteristics of ?-catenin accumulating cell clusters in adaCP, which may represent a tumor stem cell niche and might contribute to tumor recurrence. The potential impact of these special cell groups in regard to future CP management, including postoperative follow-up and additional treatment remains to be explored.
EVALuna2:7205